Profil Hemoglobin, Trombosit, dan Rasio Neutrofil Limfosit pada Pasien Kanker Kolorektal: Studi Deskriptif di RSUP Haji Adam Malik Medan - Simatupang, Ruth Vanessa; Katharine; Sinaga, Bintang Yinke Magdalena; Abdillah, Hafaz Zakky (Jurnal Kedokteran Meditek, 2025)
Introduction: Colorectal cancer is a global health problem with an increasing incidence. Monitoring cancer stage is crucial as it is closely related to therapeutic decisions, prognosis, and patient survival. Simple hematological parameters, such as hemoglobin, platelet count, and neutrophil-to-lymphocyte ratio, may aid in clinical evaluation. Objective: This study aimed to describe the profiles of hemoglobin, platelet count, and neutrophil-to-lymphocyte ratio in patients with colorectal cancer. Methods: The study employed a descriptive observational method with a cross-sectional approach. Secondary data were obtained from the medical records of 141 patients using the total sampling method. Data analysis was performed using descriptive statistics.  Results: Anemia was found in 83% of patients, with a higher incidence at higher stages. Normal platelet counts were observed in 80% of patients, with decreasing proportions in higher stages. Elevated NLR was found in 78% of patients and was more frequent at higher stages of disease.  Conclusion: These findings indicate the presence of anemia and a systemic inflammatory response, but not thrombocytosis. This research highlights the potential of these simple biomarkers in monitoring cancer stages and treatment strategies.